RETRACTED: Optimization of geometrical parameters of the heat receiver of a solar air heating collector - Uzbekov Mirsoli; Kuchkarov Akmal; Boynazarov Bekzod; Toxirov Muxammadrafiq; Muminov Shermuhammad (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001